Soybean Production in Florida - D. L. Wright; J. A. Ferrell; Santosh Sanjel; I. Small (EDIS)
This publication discusses land preparation and planting, fertilization, crop residue management, irrigation, disease and nematode management, variety selection, weed control, insect management, and harvesting and storage for soybean production in Florida. Written by D. L. Wright, J. A. Ferrell, S. Sanjel, and I. Small, and published by the UF/IFAS Agronomy Department, revised July 2022.